2005
DOI: 10.1139/x05-048
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of thinning and fertilization on growth of red fir in northeastern California

Abstract: To determine the impact of fertilization and thinning on growth and development of red fir (Abies magnifica A. Murr.) stands, we established an experiment in a 60-year-old stand using a 2 × 3 factorial design with nitrogen-fertilized and nonfertilized treatments and three stocking levels. Plots were established in 1976 and were measured every 5 years for 26 years. The periodic annual increment in basal area was 97%, 51%, 38%, and 33% greater in fertilized trees than in nonfertilized trees during the first, sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
(18 reference statements)
2
11
2
Order By: Relevance
“…This pattern could result from reduced intraspecific competition for soil resources and generally better tree vigour. However, this result disagrees with studies by Yang [18] and Zhang et al [42] which reported that nitrogen loadings increased tree mortality.…”
Section: Fertilization and Tree Mortalitycontrasting
confidence: 99%
See 3 more Smart Citations
“…This pattern could result from reduced intraspecific competition for soil resources and generally better tree vigour. However, this result disagrees with studies by Yang [18] and Zhang et al [42] which reported that nitrogen loadings increased tree mortality.…”
Section: Fertilization and Tree Mortalitycontrasting
confidence: 99%
“…We expected that by increasing tree growth, fertilization would also increase self-thinning mortality due to higher intraspecific competition [42]. Contrary to our hypothesis, fertilization did not increase tree mortality in controls or low intensity thinned plots.…”
Section: Fertilization and Tree Mortalitycontrasting
confidence: 95%
See 2 more Smart Citations
“…A pulsed fertilization 1995 1996 1997 1995 1996 1997 1995 1996 1997 1995 1996 1997 Ring width (mm) The dashed lines show the ring widths (adjusted for covariates age and DBH) for the entire data set for the 2 sites. Solid horizontal line: median; box: 25th to 75th percentiles; whiskers: 10th to 90th percentiles; dots: data points beyond the whiskers experiment on red fir Abies magnifica in California produced 20 to 50% annual increases in volume growth during the first 10 yr after fertilizer was added at 30 g N m -2 (Zhang et al 2005). Nemani et al (2003) reported an average increase of net primary production of 6.6% yr -1 for the period from 1983 to 1999 for the boreal zone.…”
Section: Discussionmentioning
confidence: 99%